Systematization andf critical analysis of centers and practices in order to suggest improvements in the professional practices of the administration program at Uniminuto - Artunduaga Lizcano, Flover; Camacho Sanabria, Carlos Julio; Montaño Martínez, Mónica (2021)
The present research focuses on analyzing the students´ professional practices, particularly the practice centers, together with the competences that are intended to be developed from the study plans. Such analysis is considered a systematic, rigorous and collaborative work that could improve both the professional practices themselves, as well as the achievement of professional competences in its broadest sense. "The concept of competence encompasses not only the capacities required for the exercise of a professional activity, but also a set of behaviors, analytic skills, decision making abilities, information transfer, etc. which are considered necessary for the full performance of the occupation (INEM, 1995).